O Ariane Mnouchkine a jej umení (On the art of Ariane Mnouchkine) - Anna A. Hlaváčová (Ostium, 2015)
Based on the author’s assistantship experience with Théâtre du Soleil during the rehearsal process of Les Atrides in 1990, this study offers an insight into the aesthetics and working strategy of the French theatre director Ariane Mnouchkine. The study focuses on the relationship of the Théâtre du Soleil to the oriental theatre sources, seeking to prove that it cannot be reduced to quotations of oriental elements in Mnouchkine’s works. In fact, the lessons from the various oriental forms are integrated into her artistic thought to the point that is no more possible to isolate the “oriental details” as they participate with all the rest on the creation of the exact stage metaphor.